Penguatan Teori Keperawatan Dan Kebidanan Dalam Melaksanakan Asuhan Kepada Pasien Di Masa Pandemic Covid-19 - Richa Noprianty; Raden Nety Rustikayanti; Cucu Rokayah; Dewi Nurlaela; Desi Wijayanti Eko Dewi; Pujiati Setyaningsih (JCOMENT (Journal of Community Empowerment), 2021)
Health services during the covid-19 pandemic are required to provide comprehensive care to clients while maintaining strict health protocols. This condition presents challenges for health workers, especially nurses and midwives in implementing theoretical concepts that are integrated into patient care. The purpose of this community service is to refresh the existing theory so that the quality of service to patients is achieved. The activity method is done hybrid (online and offline). The provision of Nursing and Midwifery theory material is done online through zoom. Participants present were nurses and midwives with the category as Clinical Instructor (CI). The implementation technique is done in four stages, namely: the first stage examines the level of knowledge of nurses and midwives with pre test through google form, the second stage is done sharing and refreshing materials, the third stage is broadcasting video simulation of theory implementation into client care and provide post test, and the fourth stage is making a visit to the hospital to see the application of theory in caring for patients. The results of the activity showed an increase in understanding of the theory of… Result of this devotion to the community programs is a video simulation certified IPR, monograph book with ISBN and IPR, online mass media publications (tribun jabar) and journal publications.